(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Atherosclerosis, which causes the coronary arteries to thin or become blocked, is the main cause of coronary artery disease (CAD), which is a major cause of death and disability globally. The oxidative breakdown of lipids, a process known as lipid peroxidation, is crucial in the development of coronary artery disease (CAD). Exploring the molecular indicators of lipid peroxidation and its implications for disease development and therapy, this research analyzes the link between CAD and lipid peroxidation. The results demonstrate a robust association between the severity of CAD and higher levels of lipid peroxidation by-products, including malondialdehyde (MDA). In order to enhance clinical results, the research suggests antioxidant treatments and stresses the importance of early oxidative stress marker detection.